Safe vs Unsafe Crosswalks: Assessing the Factors Related to Pedestrian Safety - Theodosiou, Zenonas; Voutsa, Maria C.; Constantinou, Constantinos; Lanitis, Andreas (My University, 2023)
Due to the high number of injuries at crosswalks, the creation of smart applications is imperative to timely inform and protect citizens while crossing. The development of accurate applications first requires defining the factors that affect the safety of a pedestrian crossing. This paper presents a preliminary study on crosswalk safety as an effort to help develop automatic methods for assessing safety as well as Virtual Reality (VR) tools incorporating different danger scenarios in crosswalks. The study was based on a questionnaire where 101 regular pedestrian citizens answered various questions about crossing safety and then evaluated the safety of various crosswalks represented in a series of images. The results show that parked vehicles, the presence of obstacles, rubbish, damages, and holes on crosswalks play an important role in pedestrians' safety. In addition, a number of images used in the study were statistically evaluated by the participants as depicting unsafe crosswalks and can be used as examples when collecting data.
Keywords: annotated datasets; pedestrian safety; safe cross- walks